ChemInform Abstract: Mild Hydrothermal Crystal Growth, Structure, and Magnetic Properties of Ternary U(IV) Containing Fluorides: LiUF5, KU2F9, K7U6F31, RbUF5, RbU2F9, and RbU3F13. Issue 33 (19th August 2014) - Yeon, Jeongho; Smith, Mark D.; Tapp, Joshua; Moeller, Angela; zur Loye, Hans‐Conrad
Abstract Uranium in (I) is reduced from U6+ to U4+ in the presence of Cu(OAc)2.